An SO(3)-Monopole Cobordism Formula Relating Donaldson and Seiberg-Witten Invariants - Feehan, Paul (Memoirs of the American Mathematical Society Ser., 2019)
The authors prove an analogue of the Kotschick-Morgan Conjecture in the context of SO(3) monopoles, obtaining a formula relating the Donaldson and Seiberg-Witten invariants of smooth four-manifolds using the SO(3)-monopole cobordism. The main technical difficulty in the SO(3)-monopole program relating the Seiberg-Witten and Donaldson invariants has been to compute intersection pairings on links of strata of reducible SO(3) monopoles, namely the moduli spaces of Seiberg-Witten monopoles lying in lower-level strata of the Uhlenbeck compactification of the modu.